Pelatihan “Peer Educator” dalam Upaya Penanganan Gizi Lebih Pada Remaja - K., Iriyani; Ratih Wirapuspita Wisnuwardani; Suryaningsi (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2024)
Community service aims to improve adolescent knowledge with the peer educator method at SMP Negeri 2 Samarinda. The technique used is classroom action research with a cross-sectional approach. The supporting partners for this service are the principal, teachers, and 53 students. The instrument used is a questionnaire given as a pre-test and post-test before and after being given nutrition education with a total of 20 multiple-choice questions about balanced nutrition knowledge. This community service was carried out in June-August 2024. To see the difference in knowledge scores before and after being given nutrition education, the Paired Sample T-Test was used. The results of the study showed that there was a significant difference (p = 0.001) in knowledge scores before and after being given balanced nutrition education. The results showed an increase in the average knowledge from 54.62 ± 15.65 to 76.98 ± 5.40 with a difference of 22.36 ± 14.19. This shows that nutrition education training with the peer educator method is effective in improving student knowledge at SMP Negeri 2 Samarinda.